2010
DOI: 10.1016/j.eururo.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Laparoscopic and Open Radical Nephroureterectomy in a Contemporary Group of Patients: Are Recurrence and Disease-Specific Survival Associated with Surgical Technique?

Abstract: Background Open radical nephroureterectomy (ORN) is the current standard of care for upper tract urothelial carcinoma (UTUC), but laparoscopic radical nephroureterectomy (LRN) is emerging as a minimally invasive alternative. Questions remain regarding the oncologic safety of LRN and its relative equivalence to ORN. Objective Our aim was to compare recurrence-free and disease-specific survival between ORN and LRN. Design, setting, and participants We retrospectively analyzed data from 324 consecutive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 18 publications
5
47
1
1
Order By: Relevance
“…Another retrospective study of 324 consecutive patients treated with radical nephroureterectomy found no evidence to indicate that oncologic control was differentially compromised in patients treated with laparoscopic surgery as compared to those treated with open surgery. 22 Collectively, these results show that the laparoscopic procedure produces the same oncologic results in upper urinary tract TCC patients as the open surgery.…”
Section: Discussionsupporting
confidence: 52%
“…Another retrospective study of 324 consecutive patients treated with radical nephroureterectomy found no evidence to indicate that oncologic control was differentially compromised in patients treated with laparoscopic surgery as compared to those treated with open surgery. 22 Collectively, these results show that the laparoscopic procedure produces the same oncologic results in upper urinary tract TCC patients as the open surgery.…”
Section: Discussionsupporting
confidence: 52%
“…The diminished use of laparoscopy in Eastern Canada (36%) compared to western (60%) and central (64%) regions may reflect a delayed adoption of laparoscopy in general, or a hesitation to adopt this technique specifically for nephroureterectomy. We now know from our own collaboration 15 and from other series 6,16,17 that the oncologic control for laparoscopic and open nephroureterectomy appears to be the same, but this was previously debated. Interestingly, the rate of laparoscopic cases done in Canada in the 10-year study period was much higher than the number reported in the largest multi-institutional series published, where only 28%% (270/1249) of patients from 9 centres underwent laparoscopic nephroureterectomy from 1987 to 2007.…”
Section: Discussionmentioning
confidence: 99%
“…It would appear from multiple retrospective series, for example, that laparoscopic nephroureterectomy is equivalent to open nephroureterectomy, but this has not been evaluated prospectively. [4][5][6][7] The most recent EAU guidelines state that there is limited data for laparoscopic versus open nephroureterectomy (grade B evidence), lymphadenectomy (Grade C evidence), and technique of bladder cuff excision (Grade C evidence). Other critical questions, such as the use of perioperative chemotherapy, have even less evidence.…”
Section: Introductionmentioning
confidence: 99%
“…UUT-UCC is a biologically aggressive disease with a high potential for recurrence and death [3]. Up to 60% of UUT-UCCs are invasive at diagnosis compared with only 15-25% of bladder tumours [4].…”
Section: Introductionmentioning
confidence: 99%